Strategies for developing critical thinking through blended foreign language learning - Yildiz, Ümit; Hotsynets, Iryna; Sosiak, Myroslava; Diachenko, Olena; Volovyk, Larysa (Universidad de Carabobo, 2025)
The relevance of the study is determined by the need to implement modern educational technologies that develop students’ critical thinking when studying foreign languages. The aim of the research was to investigate the impact of the blended learning on the development of these skills. The research employed the following methods: questionnaire surveys, testing, comparative analysis, observation, and pedagogical experiment. Testing was carried out using the Watson-Glaser Critical Thinking Appraisal (WGCTA) and California Critical Thinking Disposition Inventory (CCTDI) methods, as well as statistical analysis of the results. The results showed that students in the experimental group improved their critical thinking scores by +7.8 points, while the increase was only +2.6 points in the control group. It was concluded that blended learning effectively contributes to the development of cognitive skills through a combination of traditional and digital methods. The academic novelty is the identified key components of blended learning that have the greatest impact on critical thinking, such as reflective tasks and multimedia projects. Further research prospects include the integration of mobile technologies and the analysis of their impact on other aspects of the educational process.
Keywords: blended learning; critical thinking; development methods; educational strategies; foreign languages